2017
DOI: 10.1016/j.cgh.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Improved Long-term Outcomes of Patients With Inflammatory Bowel Disease Receiving Proactive Compared With Reactive Monitoring of Serum Concentrations of Infliximab

Abstract: BACKGROUND & AIMS Monitoring serum concentrations of tumor necrosis factor antagonists in patients receiving these drugs as treatment for inflammatory bowel disease (IBD), also called therapeutic drug monitoring, is performed either after patient loss of response (reactive drug monitoring) or in patients in clinical remission whose drug has been titrated to a target concentration (proactive drug monitoring). We compared long-term outcomes of patients with IBD undergoing proactive vs reactive monitoring of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(161 citation statements)
references
References 27 publications
4
153
0
4
Order By: Relevance
“…There was, however, potential for confounders in this study. Another retrospective observational study found significantly lower likelihood of treatment failure (HR 0.16, P < .001), hospitalisation (HR 0.16, P < .001), surgery (HR 0.30, P = .017), development of anti‐drug antibodies (HR 0.25, P = .025) and serious infusion reactions (HR 0.17, P = .023) with proactive vs reactive TDM‐guided infliximab dosing …”
Section: Resultsmentioning
confidence: 99%
“…There was, however, potential for confounders in this study. Another retrospective observational study found significantly lower likelihood of treatment failure (HR 0.16, P < .001), hospitalisation (HR 0.16, P < .001), surgery (HR 0.30, P = .017), development of anti‐drug antibodies (HR 0.25, P = .025) and serious infusion reactions (HR 0.17, P = .023) with proactive vs reactive TDM‐guided infliximab dosing …”
Section: Resultsmentioning
confidence: 99%
“…Reactive therapeutic drug monitoring is emerging as the new standard‐of‐care for optimizing anti‐TNF therapy in inflammatory bowel disease (IBD) . Recent studies have demonstrated that proactive therapeutic drug monitoring of infliximab with drug titration to a therapeutic window is associated with favorable long‐term therapeutic outcomes in IBD and may be superior to reactive therapeutic drug monitoring . Moreover, many exposure‐response relationship studies have shown that higher serum anti‐TNF drug concentrations are associated with better clinical outcomes in IBD, suggesting that it is maybe time to go beyond from a ‘treat‐to‐target’ to a ‘treat‐to‐trough’ therapeutic approch .…”
Section: Introductionmentioning
confidence: 99%
“…En pacientes en tratamiento con IFX en esquema de mantención, dos estrategias han sido sugeridas en la práctica clínica 18,23, . Por una parte, la MTF ha sido planteada cuando los pacientes presentan evidencias de actividad inflamatoria, lo que permite definir la mejor estrategia terapéutica siendo esta decisión más costo efectiva que escalar de manera empírica 31,32 .…”
Section: Grupo Bunclassified
“…La monitorización terapéutica del fármaco (MTF), definida como la evaluación de la concentración de la droga y de los niveles de anticuerpos contra éste, ha demostrado ser más efectiva que el manejo estándar en términos de resultados clínicos y costo efectividad, logrando de esta manera una terapia personalizada [14][15][16][17][18][19][20][21][22][23] . Pese a estos resultados, no existen publicaciones nacionales que hayan evaluado la monitorización de IFX y ATI y su efecto en pacientes con EII.…”
unclassified